Monetary Policy and Commercial Bank Lending to the Real Sector in Nigeria: A Time Series Study - ., Ogolo; Magnus, Tamunotonye (American Finance & Banking Review, 2018)
This study empirically examined the effects of monetary policy on commercial banks lending to the real sector from 1981 – 2014. The objective was to examine the effectiveness of monetary policy in channeling bank credit to the real sector. Annual time series data were sourced from Central Bank of Nigeria statistical bulletin. Two multiple regression models were specifically estimated with the aid of Software Package for Social Sciences. The study modeled commercial banks credit to agricultural and manufacturing sector as the function of interest rate, monetary policy rate, treasury bill rate, exchange rate, broad money supply and liquidity ratio. The result shows collinearity that corresponds with the Eigen value condition index, and variance constant are less than the required value. The Durbin Watson statistics shows the absence of multiple auto correlation and negative autocorrelation, while the variance inflation factors indicate the absence of auto-correlation. The regression results from model one found that interest rate, monetary policy rate have positive relationship with commercial banks lending to the agricultural sector while Treasury bill rate, exchange rate, broad money supply and liquidity ratio have negative effect on the dependent variable. Model two found that interest rate, Treasury bill rate, exchange rate, broad money supply and liquidity ratio have negative effect on commercial banks lending the manufacturing sector while monetary policy rate have positive relationship with the dependent variable. We recommend that monetary policy should be harmonize with bank lending objectives to enhance commercial banks lending to the real sector of the economy and that management of commercial banks should formulate policies of managing the negative effect of monetary policy variables on its lending.